Liver cirrhosis with its complications: Case report in a young female patient - Muhammad Hanun Mahyuddin; Ulaa Haniifah (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Liver cirrhosis is a chronic disease characterized by the presence of fibrosis and regeneration of nodules in the liver, the consequence of which is the development of portal hypertension and liver failure. Usually associated with infectious infectious diseases such as viral hepatitis, alcohol consumption, metabolic syndrome, autoimmune processes, storage diseases, toxic substances and drugs. Major complications include gastrointestinal variceal bleeding, ascites, spontaneous bacterial peritonitis infection, hepatorenal syndrome, hepatic encephalopathy, and hepatocellular carcinoma. A 23-year-old woman comes to the ER, dr. Soegiri Lamongan with complaints of vomiting blood. The patient also complained of black bloody stools. Referred patient from Intan Medika Hospital with the initial complaint of vomiting blood more than 5 times (Â± equivalent to one medium drinking bottle) four days ago. On examination also found anemic conjunctiva and found splenomegaly. On abdominal ultrasound examination, the liver was shrunken, the edges were obtuse angles, partially irregular, parenchymal echo intensity was heterogeneous, v.hepatica was normal, liver fibrosis staging was 11.81 kPa, no masses or nodules were seen. The conclusion on endoscopic examination was the presence of grade III esophageal varices, congestive gastropathy, and erosive gastritis. Liver cirrhosis is a disease that has various etiologies. Early diagnosis and appropriate treatment in cirrhotic patients with complications is one way to improve patient survival